A first evaluation of water resource conditions after an environmental reclamation effotr at a former degraded coal mining área in Southern Brazil - CARDOSO, Albert Teixeira (2021)
In southern South America, Brazil, in the state of Santa Catarina, the neglect and lack of environmental supervision during coal mining caused the contamination of surface and groundwater by acid mine drainage (AMD). By the force of the local law, environmental reclamation actions in these abandoned areas have been carried. A scientific work of monitoring and assessment of the water resources within these areas has never been developed, as the efficacy of the reclamation strategies has never been discussed. This work aims to fill this gap by presenting and analyzing the environmental reclamation strategy of a former degraded coal mining area and its impacts on local water resources. The water monitoring plan in Area IV’s was carried out in groundwater, and in lentic (ponds) and lotic (rivers) environments of surface waters, fourteen monitoring campaigns were conducted. The results showed that upstream and downstream river points have different water qualities, with the downstream points having water quality, still affected by past mining activities. From the surface water perspective, the reclaiming method adopted was effective in three of the four ponds, presenting problems only in the downstream one. Two hypotheses were proposed; the first hypothesis is that contamination happens due to leaching of the material that still remains on the ponds’ banks into the water. Another hypothesis is that the contamination comes from the upstream groundwater inflow into the pond, which runs through the entire area before reaching the pond. Those results serve to further access the actual monitoring perspectives as well as to better develop future reclaiming strategies.